Use of Enoxaparin to Counteract COVID-19 Infection and Reduce Thromboembolic Venous Complications: A Review of the Current Evidence - Drago, Filippo; Gozzo, Lucia; Li, Li; Stella, Andrea; Cosmi, Benilde (Frontiers in Pharmacology, 2020)
The impact of the COVID-19 pandemic has been dramatic worldwide, with China, Italy and now US at its epicenter. Researchers and clinicians are studying and testing different approaches in the attempt to prevent the infection and minimize its severity. Major efforts are focused on optimizing mechanical ventilation, antiviral and supportive treatment; however, the role of heparin and low molecular weight (LMW) heparin in this setting has been largely overlooked. This review summarizes the available evidence about the role of heparan sulfate as a key entry mechanism for SARS-CoV-2; the efficacy of heparin and LMW heparin in counteracting its entry into the cell; the recent experimental findings obtained in in-vitro studies using the LMW heparin enoxaparin Inhixa®; the role of heparin and LMW heparin in modulating the cytokine storm and the evidence for the use of LMW heparin in the prevention and treatment of the thromboembolic complications of COVID-19. The available evidence suggests that LMW heparin appears as a promising tool in the treatment of COVID-19. Whether its systematic use is associated with a reduction in complications and ultimately mortality of these patients is being tested in several studies starting worldwide.